2022
DOI: 10.1007/s11356-022-19804-9
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid-induced pathophysiological damage in the midgut of Locusta migratoria (Orthoptera: Acrididae) in the field

Abstract: Neonicotinoids are modern insecticides widely used in agriculture worldwide. Their impact on target (nervous system) and non-target (midgut) tissues has been well studied in bene cial insects including honeybees. However, their effects on pest insects on the eld are comparably rarely described. Here, we have studied the effects of the neonicotinoid imidacloprid on the midgut of the pest insect Locusta migratoria caught in the eld. We found that in the midgut of imidacloprid-exposed locusts the activity of enzy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Likewise, we have not come across any direct reference on the histopathological effects of imidacloprid on midgut of 4 th -instar larvae of S. littoralis. However, in our current study, the histological changes induced in the midgut of the 4 th larval instars of S. littoralis treated with imidacloprid was similar to these obtained by [52] for the midgut of Locusta migratoria treated with the same insecticide. Also, the histopathological alterations of imidacloprid and tannic acid on the larvae of Culex pipiens showed that the treated larvae had cytopathological alterations of the midgut epithelium, muscular layers, and epithelial cells [53].…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, we have not come across any direct reference on the histopathological effects of imidacloprid on midgut of 4 th -instar larvae of S. littoralis. However, in our current study, the histological changes induced in the midgut of the 4 th larval instars of S. littoralis treated with imidacloprid was similar to these obtained by [52] for the midgut of Locusta migratoria treated with the same insecticide. Also, the histopathological alterations of imidacloprid and tannic acid on the larvae of Culex pipiens showed that the treated larvae had cytopathological alterations of the midgut epithelium, muscular layers, and epithelial cells [53].…”
Section: Discussionsupporting
confidence: 90%
“…The P450 enzymes conjugate with oxygen molecules and obtain energy from NADPH to penetrate oxygen into the substrate/insecticide. P450 monooxygenase enzyme activity has been linked to insecticide resistance in various studies (Siegfried and Scot 1992;Pridgeon et al 2003; Wolfe and Scharf 2022) and regular prolonged intoxication results in elevated enzyme activity (Hu et al 2020;El-Samad et al 2022). In the current study, continuous long-term exposure to imidacloprid and clothianidin disrupted the P450 system in cockroaches and the insecticide-induced changes in the activities of enzymes involved in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the harmful effects of metal NPs on the reproductive system using insects as bioindicators has recently come to light in order to evaluate environmental pollution and comprehend critical biological problems [ 12 , 13 ]. Recently, migratory locusts, Locusta migratoria (Linnaeus, 1758), have received a lot of attention for their use in environmental toxicity assessments because they have inherent advantages, such as a short life cycles and non-specific living demands [ 12 , 14 , 15 ]. Significantly, the immune system of L. migratoria comprises humoral-based and cell-mediated immune reactions, including the synergy of hemocytes, fat bodies, and circulating hemolymph peptides for the elimination or deactivation of xenobiotics [ 15 ].…”
Section: Introductionmentioning
confidence: 99%